Clinical and biochemical effect of laser as an adjunct to non‐surgical treatment of chronic periodontitis. (3rd May 2021) - Jiang, Yiyang; Feng, Jie; Du, Juan; Fu, Jingfei; Liu, Yitong; Guo, Lijia; Liu, Yi
Abstract: Objectives: To evaluate the clinical and biochemical efficacy of laser therapy as an adjunct to non‐surgical treatment in chronic periodontitis. Methods: A systematic search was performed through the PubMed, EMBASE, and Cochrane Library for eligible articles published as of May 2, 2020, supplemented by information search in the System for Information on Programme Literature in Europe and a manual literature search. Only randomized controlled trials (RCTs) used to compare the adjunctive use of laser and non‐surgical treatment alone with an observation period of at least 6 months were included. Results: Sixteen RCTs with a total of 525 subjects were included. Meta‐analysis suggested that the additional use of laser to scaling and root planing (SRP) showed significant superiority over SRP alone among most of clinical parameters involved. Regarding the GCF, although volume in the laser group was lower at week 4 and 12, no significant difference was found regarding the cytokines level. Subgroup analysis revealed that the combined therapy produced no significant difference in PD, CAL and PI at most time points for studies in respect to smokers. No treatment‐related adverse events had been reported in the included studies. Conclusions: Pooled analysis suggested that laser‐assisted non‐surgical treatment improved clinical outcome to SRP alone in the management of non‐smoking chronic periodontitis patients.